Actividad sérica de la adenosina deaminasa (ADA) en la tuberculosis pulmonar - Espinoza M., Oswaldo (2000)
Serum adenosine deaminase enzyme determinations were perfonned in 74 adult individuals of both sexes, consisting of 29 adult patients with active pulmonary tuberculosis, and 45 voluntary healthy individuals with no recent or past tuberculosis history, who constituted thecontrol group. The mean value of ADA enzyme serum activity in the group of patients with pulmonary tuberculosis was 47,89 + 6,05 U/L, and in the group of healthy individuals, 18.84 + 6.16 U/L. The difference between the means of serum ADA enzyme activity in the tuberculosis patients and the mean value of the control group was statistically significant (p < 0,001). The validation criteria showed the following results: sensitivity, 100%; specificity, 91.11%; efficiency, 94.59%; predictive value of positivity, 87,88%; predictive value of negativity, 100% .In the cases with high prevalence value, serum ADA test can be a simple test of high diagnostic value. We determined serum ADA in patients with pulmonary tuberculosis and in healthy individuals with the purpose of evaluating utility of serum ADA test in pulmonary tuberculosis diagnosis.